PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI INTERNET TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR - Dwi Utami; Irfan Julianta; Siti Halimah (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2021)
The aimed of this study were:(1) To determine the effect of using internet technology on learning motivation of Social Studies Subjects in Class VIII students at SMP Negeri 3 Sampit in the Academic Year 2020/2021(2) To determine the effect of using internet technology on student learning outcomes of Social Studies subjects in. VIII at Class Students SMP Negeri 3 Sampit in the Academic Year 2020/2021.The population in this study were Class VIII students of SMP Negeri 3 Sampit in the Academic Year 2020/2021, totaling 322 students and taken as a sample of 20%, namely 70 students with the Proportional Random Sampling technique. The data analysis technique used a simple linear regression analysis technique.Based on the results of simple linear regression analysis, they ware:(1) There was a significant effect between the use of Internet Information Technology and Learning Motivation in Class VIII Students in Room 1 to 9 at SMP Negeri 3 Sampit in the Academic Year 2020/2021. With the value of tcount> from ttable, which was 12,728>1,995.(2) There was  no significant effect between the use of internet information technology on learning outcomes in Class VIII Students from Room 1 to 9 at SMP Negeri 3 Sampit for the Academic Year 2020/2021. With the value of tcount> from ttable, that was 1.019<1.995.